Total Blind Resilience of Parents Who Have Total Blind Children with Blindness - Barkah Kadia; Baharuddin Yusuf; Citrawanti Oktavia (JOM, 2024)
Being a parent of a blind child requires various abilities, one of which is resilience. Resilience is a universal capacity that enables individuals, groups, or communities to prevent, minimize, or resist damaging influences when faced with disaster or adversity. According to Grotberg (1995), resilience is the human ability to face, overcome and become strong when facing obstacles and obstacles. This research aims to describe the factors that support the resilience of parents of totally blind children at the National School for the Blind. This research uses qualitative methods with case studies. Data collection techniques involve interviews, observation, and secondary data. The subject of this research was a parent who had a totally blind child.